2019
DOI: 10.1002/jmri.26903
|View full text |Cite
|
Sign up to set email alerts
|

Dual‐frequency MR elastography to differentiate between inflammation and fibrosis of the liver: Comparison with histopathology

Abstract: Background Differentiation between inflammation and fibrosis is an important clinical distinction in patients with chronic liver disease, which has been difficult so far with MR elastography. Purpose To investigate whether dual‐frequency MR elastography can estimate necroinflammation of the liver and improve diagnostic performance for the staging of liver fibrosis. Study Type Retrospective. Subjects In all, 30 patients (14 males, 16 females) with chronic liver disease. Field Strength/Sequence 1.5T/dual‐frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“… 103 Sofue et al measured the elastic moduli of 30 patients with various chronic liver diseases, including NASH, using MRE at vibration frequencies of 60 Hz and 80 Hz. 104 They found that the elastic moduli imaged at 80 Hz were always higher than those at 60 Hz and that the difference, ΔG, correlated strongly with the histological activity grade. The modulus at 80 Hz correlated more strongly with the activity grade than the modulus at 60 Hz, and the correlation became even stronger when ΔG was taken into account.…”
Section: Quantification Of Inflammationmentioning
confidence: 97%
See 1 more Smart Citation
“… 103 Sofue et al measured the elastic moduli of 30 patients with various chronic liver diseases, including NASH, using MRE at vibration frequencies of 60 Hz and 80 Hz. 104 They found that the elastic moduli imaged at 80 Hz were always higher than those at 60 Hz and that the difference, ΔG, correlated strongly with the histological activity grade. The modulus at 80 Hz correlated more strongly with the activity grade than the modulus at 60 Hz, and the correlation became even stronger when ΔG was taken into account.…”
Section: Quantification Of Inflammationmentioning
confidence: 97%
“…103 Sofue et al measured the elastic moduli of 30 patients with various chronic liver diseases, including NASH, using MRE at vibration frequencies of 60 Hz and 80 Hz. 104 They found that the elastic moduli imaged at 80 Hz were always higher than those at 60 Hz and that the Y. Tsujita et al…”
Section: Multifrequency Mr Elastographymentioning
confidence: 98%
“…Thirteen studies 30,[53][54][55][56][57][58][59][60][61][62][63][64] reported in 15 publications 30,31,[53][54][55][56][57][58][59][60][61][62][63][64][65] were included in the DTA review. Two studies 30,59 reported in four publications 30,31,59,65 were evaluations of LiverMultiScan and 10 studies [53][54][55]57,58,[60][61][62][63][64] were evaluations of MRE. One study 56 was an evaluation of LiverMultiScan and MRE.…”
Section: Studies Included In the External Assessment Group Reviewmentioning
confidence: 99%
“…In order to induce shear waves in the liver, a form of vibrating device, called a transducer, is strapped to the patient's ribcage. When performing liver MRE in human subjects, a frequency of 60 Hz is typically used, at least for fibrosis staging [68], while a slightly larger range of frequencies have been used in exploratory investigation inflammation staging [69,70].…”
Section: Introducing Motion Into the Livermentioning
confidence: 99%